Creative nonfiction : a reader - Hidalgo, Cristina Pantoja (Diliman Quezon City, Philippines : University of the Philippines Press, 2005)
Creative nonfiction is the most popular form of creative writing today and in the opinion of some, the most important.
Preface -- Acknowledgements -- Reportage -- Feature Articles/Essays -- Features Articles/Reviews -- Interview Stories/ Character Sketches/Profile -- Travel Essays/Travel Narratives -- Personal Recollection/Memoir -- Epilogue -- The Editor.
Keywords: REPORTAGE LITERATURE